2006
DOI: 10.1063/1.2218044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen plasma treatment on reduction of contact resistivity at pentacene/Au interface

Abstract: We report the reduction of contact resistivity between Au and pentacene by O2 plasma treatment. Contact resistance dramatically reduced from 5.65to0.22MΩcm by the treatment. O2 plasma treatment transformed Au to AuOx, increasing the surface energy from 45.1to71.5mJ∕m2. Molecular adsorption geometry of pentacene on AuOx changed from a planar structure to an upright type, improving crystallinity and molecular packing. Thus, defects and traps at the interface were reduced, decreasing the contact resistance betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…To enhance the performance of the BC OFETs, it is essential to reduce the contact resistance by lowering the energy barrier. For this purpose, several methods for treating S/D electrodes have been reported, such as O 2 plasma [8], self-assembled monolayers (SAMs) with a dipole moment [9e11], and a few nanometer thick buffer layer with a transition metal oxide (TMO) [12e14], which can adjust the work function of S/D electrodes. In particular, the use of solutionprocessible TMOs is a favourable method because (i) they can be applied easily to all kinds of metals, (ii) their low process temperature is suitable for flexible or stretchable device fabrication, and (iii) they have deep highest-occupied-molecular-orbital (HOMO) and lowest-unoccupied-molecular-orbital (LUMO) energy levels that are sufficient to facilitate carrier injection into organic semiconductors [15e17].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the performance of the BC OFETs, it is essential to reduce the contact resistance by lowering the energy barrier. For this purpose, several methods for treating S/D electrodes have been reported, such as O 2 plasma [8], self-assembled monolayers (SAMs) with a dipole moment [9e11], and a few nanometer thick buffer layer with a transition metal oxide (TMO) [12e14], which can adjust the work function of S/D electrodes. In particular, the use of solutionprocessible TMOs is a favourable method because (i) they can be applied easily to all kinds of metals, (ii) their low process temperature is suitable for flexible or stretchable device fabrication, and (iii) they have deep highest-occupied-molecular-orbital (HOMO) and lowest-unoccupied-molecular-orbital (LUMO) energy levels that are sufficient to facilitate carrier injection into organic semiconductors [15e17].…”
Section: Introductionmentioning
confidence: 99%
“…It was also confirmed from O 1s spectra of O 2 -Au. 4 For both bare Au and O 2 -Au substrates, Au and O peak intensities exponentially decreased and C peak intensities z E-mail: jllee@postech.ac.kr increased with PEN film thickness. Negligible changes in the peak positions of Au 4f and O 1s spectra with PEN film thickness were found for both bare Au and O 2 -Au.…”
mentioning
confidence: 99%
“…3 It was reported that the contact resistance between Au and PEN could be reduced by O 2 plasma treatment on Au electrode prior to PEN deposition. 4 The surface of Au was transformed into AuO x ͑Au-O bond formation͒ when the Au surface was exposed to O 2 plasma. Enhanced crystallinity of PEN deposited on O 2 plasmatreated Au was observed.…”
mentioning
confidence: 99%
“…It is thus very easy to estimate the contact resistance from the current-voltage characteristics of such a device configuration [15,544]. For instance, a TLM scheme [106,[549][550][551][552][553] was implemented using an electrode material pattern deposited on a glass substrate with a gap between adjacent electrodes from 50 to 90 μm with an increment of 5 μm [553] and depositing the OS directly on this pattern. Total contact resistance was thus determined from the measured I-V characteristics of such OFETs.…”
Section: Interface Engineering For Os Devicesmentioning
confidence: 99%
“…In order to adjust the electrical conditions at different interfaces encountered in practice, various types of SAMs were developed in the past and used in different contexts such as patterning of nanoscale devices, corrosion prevention, and controlling surface properties [518,[552][553][554][562][563][564][565][566][567][568][569][570][571][572][573][574]. SAM modification of a metal surface offers a better possibility to improve the performance of OE devices as well [518,[562][563][564][565][566][567][568][569][570][571][572][573][574].…”
Section: Interface Engineering For Os Devicesmentioning
confidence: 99%